The Impact of Perineural Invasion and/or Lymphovascular Invasion on the Survival of Early-Stage Oral Squamous Cell Carcinoma Patients - Chen, Tseng-Cheng; Wang, Cheng-Ping; Ko, Jeng-Yuh; Yang, Tsung-Lin; Hsu, Chun-Wei; Yeh, Kuo-An; Chang, Yih-Leong; Lou, Pei-Jen (Annals of surgical oncology, 2013)
Background For early-stage oral squamous cell carcinoma (OSCC) patients, the impact of perineural invasion (PNI) and lymphovascular invasion (LVI) on disease control and survival has not been clarified. Methods The medical records of all early-stage OSCC patients who underwent curative surgery between 2004 and 2009 were reviewed. Results A total of 442 early stage patients were included in this study. There were 360 patients in group A (without PNI or LVI) and 82 patients in group B (with PNI and/or LVI). Between groups A and B patients, there were no significant differences in the 5-year disease-free survival (73.8 vs 68.7 %, p = 0.48) and overall survival (90.9 vs 86.1 %, p = 0.25). Between groups A and B patients without postoperative radiotherapy (PORT), there were no significant differences in the 5-year disease-free survival (73.8 vs 70.2 %, p = 0.51) and overall survival (90.9 vs 85.2 %, p = 0.18). Between group B patients with and without PORT, there was no significant difference in either the disease-free survival (61.1 vs 70.2 %, p = 0.98) and overall survival (88.9 vs 85.2 %, p = 0.64). Multivariate analyses revealed that PNI, LVI, and PORT could not provide significant effect on treatment outcome. Conclusions PNI and LVI were not significant risk factors for the disease control and overall survival for early stage OSCC patients. Furthermore, PORT could not provide an additional benefit for the disease control and overall survival for stages I and II OSCC patients with PNI and/or LVI.